1997
DOI: 10.1177/154079699702200303
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mentoring versus Job Coach Instruction on Integration in Supported Employment Settings

Abstract: Thirty employees at Pizza Hut were observed to examine the effects ofthree training strategies on social integration. These training strategies represented: (a) the traditional job coach model, (b) a mentoring model, and (c) the use of management and coworkers to train new employees without disabilities. This research found that employees with severe disabilities trained using the mentor model had more interactions with nondisabled coworkers than those trained using thejob coach model. The data also indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The mentor only needs to continue to attend the group (which they would have done in any case) and to take on the additional mentorship role for as long as such support is needed. Mentors in community groups are analogous to co-workers providing on-the-job support to people with disability in open employment, and it is notable that researchers have successfully recruited co-workers to provide this support (Farris & Stancliffe, 2001;Lee, Storey, Anderson, Goetz, & Zivolich, 1997;Storey, 2003).…”
Section: Transition Into Retirementmentioning
confidence: 97%
See 1 more Smart Citation
“…The mentor only needs to continue to attend the group (which they would have done in any case) and to take on the additional mentorship role for as long as such support is needed. Mentors in community groups are analogous to co-workers providing on-the-job support to people with disability in open employment, and it is notable that researchers have successfully recruited co-workers to provide this support (Farris & Stancliffe, 2001;Lee, Storey, Anderson, Goetz, & Zivolich, 1997;Storey, 2003).…”
Section: Transition Into Retirementmentioning
confidence: 97%
“…Coworker training is founded on the notion that relying on artificial support from ''outsiders'' impedes the formation of social networks. The rationale for using co-worker training rests on the increased social integration and socialisation offered through using natural supports (Lee et al, 1997). To help the person with a disability to be truly included in their chosen community group, this research suggests that ongoing support from a designated member of the group (the mentor) is preferable to the direct involvement of an outside disability professional.…”
Section: Transition Into Retirementmentioning
confidence: 99%
“…By contrast, providing a level entrance and an automatically opening door for all customers is universalistic. Similarly, assigning an agency "job coach" to a worksite is exceptionalistic, whereas a supervisory training program to ensure that supervisors have the knowledge and skill to train and supervise employees with and without disabilities (Lee, Storey, Anderson, Goetz & Zivolich, 1997) is universalistic. "Paratransit" services are exceptionalistic, although an accessible community transportation system with both scheduled route and on-demand options for all citizens is universalistic.…”
Section: The Advent Of the Social Model Of Disabilitymentioning
confidence: 98%
“…Because some research evidence has suggested that coworkers may be instrumental in facilitating the social integration of employees with disabilities (Lee, Storey, Anderson, Goetz, & Zivolich, 1997;Storey & Garff, 1999), the initial plan for analysis involved entering coworker interventions as a third step in the regression models to determine if preparing coworkers to support employees with disabilities would improve prediction of social integration over that explained by individual characteristics and workplace contact variables. However, a preliminary examination of the bivariate correlation matrix revealed that coworker interventions were not significantly related to any of the criterion variables.…”
Section: Data Analysesmentioning
confidence: 99%